Review of impact assessments on women's economic empowerment and technology adoption - CGIAR GENDER Impact Platform (CGIAR GENDER Impact Platform, 2025)
This report reviews impact assessments undertaken across the CGIAR portfolio. Impact assessments at CGIAR provide empirical evidence to help policymakers, researchers and stakeholders make informed decisions about which agricultural technologies and practices to promote, scale or invest in. These assessments can focus on short-, medium- and long-term outcomes. This report synthesizes the current body of evidence on CGIAR impact assessments focused on gender published in the CGSpace database, highlighting key insights and takeaways from these studies, focusing particularly on assessments on women’s economic empowerment and women’s adoption of agricultural technologies. The report also examines the strengths and weaknesses of the methodologies used and identifies research gaps and areas where further evidence is needed. The aim of this report is to guide future CGIAR gender research to inform solutions to close gender gaps and empower women in agri-food systems.